Correlation between chest x-ray findings and outcomes of patients with mechanical ventilation - Indah Nurhayati; Muhammad Supriatna; Kamilah Budhi Raharjani; Eddy Sudijanto (Indonesian Pediatric Society, 2013)
Background Most infants and children admitted to the pediatricintensive care unit (PICU) have respiratory distress and pulmonarydisease as underlying conditions. Mechanical ventilation may beused to limit morbidity and mortality in children with respiratoryfailure.Objective To assess a correlation between chest x-ray findingsand outcomes of patients with mechanical ventilation.Methods This retrospective study was held in Dr. KariadiHospital, Semarang, Indonesia. Data was collected from themedical records of children admitted to the PICU from Januaryto December 2010, who suffered from respiratory distress andused mechanical ventilation. We compared chest x-ray findings tothe outcomes of patients. Radiological expertise was provided byradiologists on duty at the time. Chi-square and logistic regressiontests were used for statistical analysis.Results There were 63 subjects in our study, consisting of 28 malesand 35 females. Patient outcomes were defined as survived or died,43 subjects ( 68%) and 20 subjects (3 2%), respectively. Chest x-rayfindings revealed the following conditions: bronchopneumonia48% (P=0.298; 95%CI 0.22 to 1.88), pleural effusion 43%(P=0.280; 95%CI 0.539 to 4.837) , pulmonary edema 6%(P=0.622; 95%CI 0.14 to 14.62) and atelectasis 3% (P=0.538;95%CI 0.03 to 7 .62). None of the chest x-ray findings significantlycorrelated to patient outcomes.Conclusion Chest x-ray findings do not correlate to patientoutcomes in pediatric subjects with mechanical ventilation inthe PICU of Dr. Kariadi Hospital, Semarang, Indonesia.